Law, Conflict, and Hybrid Warfare: A Teaching Imperative for a Changing World - Cynthia Alkon; Andrea Kupfer Schneider (Washington University Journal of Law and Policy, 2026)
Lawyers increasingly find themselves at the frontlines of the battlefield, just not in the traditional sense. Hybrid warfare is a conflict form that combines traditional military offensive measures with nontraditional methods, including the harnessing of legal systems to achieve strategic goals. Lawyers have always been at the frontline of typical legal risk assessment, thinking about a client’s risk of liability or regulation costs generally. Now, lawyers must stand at the ready for a lot more: lawyers must be prepared for cyber-attacks, disinformation campaigns using artificial intelligence, the use of court systems to suppress reporting or shield bad actors, and so much more. Gone are the days where traditional lawyering is the sole line of support that lawyers can offer. A lawyer’s negotiation and mediation skills must be honed and trained in hybrid warfare to be an asset to clients experiencing these events. This Essay explains what hybrid warfare is, its evolution, and how it is going to appear before public and private sector lawyers across the globe. It will cover the goals and missions of the first course seeking to train lawyers in hybrid warfare. As the world changes, as methods of combat evolve, and as client needs change accordingly, lawyers must do the same.
Keywords: #AIandLaw; #HybridWarfare; #LawAndTechnology; #CyberLaw